Lookies Cafe Online Ordering System using Gestalt principle - Zulkefli, Siti Nur Aqilah (2025)
This project is directed towards developing an Online Ordering System for Lookies Cafe, a Kuala Terengganu-based bakery business that handles cakes, bread, cookies, and tea. The system is designed to eliminate the limitations of the current ordering system, such as using WhatsApp, lack of real-time pricing, manual tracking of orders, and lack of invoice and receipt generator. Developed using the Adapted Waterfall Model, the process includes planning, analysis, design, development, testing, and documentation. The web-based application is intended to increase the speed of service, optimize order accuracy, and bring in efficient inventory and payment management to better serve Lookies Cafe's local customers. Paramount among these are decreasing customer waiting times, minimizing human error in order processing, bringing in automation in handling orders, inventory management, and payment processing. Developed with a technologically conscious customer base in mind, Lookies Cafe's system ensures precise order handling, streamlines business workflows, and provides in-depth financial monitoring and reporting capabilities. Usability testing using the System Usability Scale (SUS) showed a high satisfaction score of 85.33, meaning users were very satisfied. The functionality also received the highest mean score of 4.72, showing strong approval from users. The project concludes with suggestions for the further development of the system, such as alternate payment methods, real-time order status and helping Lookies Cafe grow in the online market arena by applying Gestalt principles to enhance design simplicity and end-user interaction.